(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Seemingly, third-instar larvae of R.fulva need to spend a very long quiescent period in the soil before moulting. Observations on this matter were carried out in jars with fine damp ground, where single egg-bearing females collected in May (n=18) discharged one egg mass. Larvae hatched 7-11 days later and moulted twice within 50 hours. Third-instar larvae didn’t leave their hatching place for 4-5 days; then, they dispersed on the jar ground without showing a clear interest for the supplied food. After further 3-4 days, most of them did hide into the ground by building a cell, which could harbour from one up to some 30 larvae; they rested in their cells for many weeks and died within, the subsequent July. A minor number of larvae moulted to the IV instar in cells and reappeared at surface 10-15 days later. Observations showed I-II instar larvae of R.fulva to be unable in leaving hatching place because of their very quick moulting. Although a similar behaviour is reported in the literature for Mastigus pilifer Kraatz (Scydmenidae), larval aggregation of this scydmenid does clearly depend upon the feeding request for a maternal secretion. Literature on Coleoptera gives an instance of delayed dispersion ofthird-instar larvae for another flower-dwelling species, Psilothrix viridicoerulea (Geoffroy) (Melyridae); on the contrary, it doesn’t include any instance of cell-building behaviour by of young larvae.